Body Mass Index Mediates the Association between Dietary Fiber and Symptomatic Knee Osteoarthritis in the Osteoarthritis Initiative and the Framingham Osteoarthritis Study. Issue 12 (5th December 2018) - Dai, Zhaoli; Jafarzadeh, S Reza; Niu, Jingbo; Felson, David T; Jacques, Paul F; Li, Shanshan; Zhang, Yuqing
ABSTRACT: Background: Dietary fiber reduces body weight and inflammation in clinical trials. It is unclear whether body mass index (BMI) and inflammation might explain the observed association between higher fiber intake and the lower risk of symptomatic knee osteoarthritis (SXKOA). Objectives: We quantified the extent to which BMI and inflammation influenced the relation between dietary fiber and SXKOA. Methods: We used longitudinal data from the Osteoarthritis Initiative (OAI) and the Framingham Offspring Osteoarthritis Study. At baseline of each study, men and women (mean age: 61 y) with or at risk of knee osteoarthritis were followed for 48 mo in the OAI. Adults (mean age: 53 y) were followed for 9.5 y in the Framingham study. Dietary fiber intake was estimated using a validated food-frequency questionnaire. Measured weight and height were used to calculate BMI. Serum high-sensitivity C-reactive protein (CRP) was measured in the Framingham study only. Incident SXKOA was defined as new onset of a combination of knee pain and radiographic osteoarthritis. We applied marginal structural models to quantify the mediation through BMI in the OAI and the sequential mediation through BMI and CRP in the Framingham study. Results: Incident SXKOA occurred in 861 knees among 2876 persons in the OAI and in 143 knees among 971 persons in the Framingham study. In persons whose fiber intake was ≥21 g/d compared with those with intakes <21 g/d, the OR (95% CI) was 0.70 (0.53, 0.91) for the overall association with SXKOA and was 0.93 (0.92, 0.95) for the mediation via BMI (per kg/m 2 ) in the OAI. In the Framingham study, the overall association was 0.57 (0.30, 1.09), the mediation through BMI (via BMI and the influence of BMI on CRP) was 0.94 (0.85, 1.02), and the mediation through CRP (per milligram per liter) was 0.99 (0.84, 1.19). Conclusion: Our findings suggest that the inverse association of fiber intake and the risk of incident symptomatic knee osteoarthritis is partially mediated by BMI.